THU0032 Predicting the Evolution of Inflammatory Arthritis in ACPA-Positive Individuals: can T-Cell Subset Help?. (23rd January 2014) - Hunt, L.; Nam, J. L.; Rakieh, C.; Emery, P.; Ponchel, F.
Abstract : Background: ACPA+ individuals with non specific musculoskeletal symptoms are at high risk of developing rheumatoid arthritis (RA). We previously demonstrated dys-regulation of T-cell subsets with loss of naïve and regulatory T-cell (Treg) in early disease. Objectives: The aim of the current study is to demonstrate the biomarker value of T-cell subset analysis for the prediction of symptom onset in ACPA+ individuals. This preliminary data aims to highlight the clinical application of T-cell subset analysis within a predictive model for rheumatoid arthritis. Methods: 64 ACPA+ individuals without clinical synovitis at recruitment were followed in the rheumatology clinic for up to 52 months. At baseline T-cell subset analysis was performed using 6 colour flowcytometry for naïve T-cell (CD4+CD45RB+CD45RA+CD62L+), Treg (CD4+CD25 high Foxp3+CD127 low ) and inflammation related cells (IRC: CD4+CD45RB+CD45RA+CD62L-). Analysis of 75 healthy controls (HC) enabled a reference group. Results: 33/64 (51.5%) patients developed clinical synovitis within a median follow-up of 6.1 months (range 1 week to 49 months). Of these 5 were diagnosed as undifferentiated arthritis (UA) and 28 meet the ACR/EULAR 2010 criteria for RA. Within those patients who progressed to synovitis T-cell subset analysis revealed disturbance from health in all 3 subsets. Both naïve T-cell frequency (p=0.003) and regulatory T-cell (p<0.0001) were reduced, while inflammation related cells (IRC, p=0.017) frequencies were increased. Groups however were not aged matched. Progression towards synovitis was associated with lower naïve (p=0.005) and Treg (p=0.004) frequency but increased IRC (p<0.0001). To develop a predictive model, naïve cells were coded (normal or reduced) according to the age-adjusted 95% CI of data obtained from the 75 HCs, and Treg / IRC using the 95%CI of the HC distribution as not related to age. Progression was associated with reduced naïve T-cells (p=0.009), reduced Treg (p=0.022) and increased IRC (p=0.001). Regression using these 3 parameters confirmed IRC (p=0.001) and naïve cells (p=0.011) as independent predictors of progression but Treg were less predictive as most patients showed clear reduction compared to HC95%CI (p=0.097). Conclusions: T-cell dys-regulation in ACPA+ individuals with non-specific musculoskeletal pain may be useful in predicting progression to inflammatory arthritis. Disclosure of Interest: L. Hunt: None Declared, J. Nam: None Declared, C. Rakieh: None Declared, P. Emery Consultant for: Abbott, BMS, Chugai, MSD, Pfizer, Roche, UCB., F. Ponchel: None Declared